2021
DOI: 10.1002/chem.202004215
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Magnetic Communication between Metal Centres: The Role of s‐Tetrazine Based Radicals as Ligands

Abstract: Although 1,2,4,5‐tetrazines or s‐tetrazines have been known in the literature for more than a century, their coordination chemistry has become increasingly popular in recent years due to their unique redox activity, multiple binding sites and their various applications. The electron‐poor character of the ring and stabilization of the radical anion through all four nitrogen atoms in their metal complexes provide new aspects in molecular magnetism towards the synthesis of new high performing Single Molecule Magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 198 publications
1
16
0
Order By: Relevance
“…Attempts to reduce the crystallization times were unsuccessful. Due to the relatively low half-wave reduction potential of the tz ligand (À0.78 V), [28] analogous reactions without the presence of areducing agent were performed. Although, upon mixing of the tz ligand (pink solution) with the [Cp* 2 Ln][(m-Ph 2 )BPh 2 ] (Ln = Dy or Gd) (yellow slurry) ad esirable colour change (dark red) was observed, no products were isolated via this synthetic route.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Attempts to reduce the crystallization times were unsuccessful. Due to the relatively low half-wave reduction potential of the tz ligand (À0.78 V), [28] analogous reactions without the presence of areducing agent were performed. Although, upon mixing of the tz ligand (pink solution) with the [Cp* 2 Ln][(m-Ph 2 )BPh 2 ] (Ln = Dy or Gd) (yellow slurry) ad esirable colour change (dark red) was observed, no products were isolated via this synthetic route.…”
Section: Resultsmentioning
confidence: 99%
“…Similar N=Nbond elongation was previously reported for tzC À -derived radical anions. [28,31] Moreover,t he shortest intramolecular Dy•••Dy distance is 7.341 (10) ,w hile the longest distance separating the diagonals is found to be 10.715(18) (Figure S3). It is noteworthy that, in this centrosymmetric Dy 4 complex, all Dy ions lie in the same plane (Figure S4), likely imposed by the planarity of the tzC À radical anion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these issues, we turned our attention towards using the relatively unexplored unsubstituted 1,2,4,5‐tetrazine (tz) as a bridging ligand. It has been shown that the very low‐lying π* LUMO of the tz ring easily favours the reduction and formation of the tz .− radical anion [28–35] . The diffuse spin orbitals of tz .− ‐based radicals are ideally suited to penetrate the core‐like electron density of the lanthanide ion and reach the shielded 4 f orbitals to promote stronger coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Copper(II)-and nickel(II)-radical complexes having a direct radical coordination bond are the best documented in the 3d-2p heterospin systems [9,[60][61][62][63][64][65][66][67][68][69][70]. There have been an increasing number of compounds showing a ferromagnetic 3d-2p coupling [75][76][77][78][79][80][81]. It is believed for a long time that axial coordination in copper(II)-nitroxide complexes displays relatively weak ferromagnetic interaction whilst equatorial coordination strong antiferromagnetic interaction [9].…”
Section: Magneto-structural Relationship and Molecular Designmentioning
confidence: 99%